Karolina's twins [large type] - Balson, Ronald H. (Balson, Ronald H. Liam and Catherine, 2016)
She made a promise in desperation. Now it's time to keep it. Lena Woodward, elegant and poised, has lived a comfortable life among Chicago Society since she immigrated to the United States and began a new life at the end of World War II. But now something has resurfaced that Lena cannot ignore: an unfulfilled promise she made long ago that can no longer stay buried. Driven to renew the quest that still keeps her awake at night, Lena enlists the help of lawyer Catherine Lockhart and private investigator Liam Taggart. Behind Lena's stoic facade are memories that will no longer be contained. She begins to recount a tale, harkening back to her harrowing past in Nazi-occupied Poland, of the bond she shared with her childhood friend Karolina. Karolina was vivacious and beautiful, athletic and charismatic, and Lena has cherished the memory of their friendship her whole life. But there is something about the story that is unfinished, questions that must be answered about what is true and what is not, and what Lena is willing to risk to uncover the past. Has the real story been hidden these many years? And if so, why? Two girls, coming of age in a dangerous time, bearers of secrets that only they could share.